The Effects of Conformational Constraints in the Polyamine Moiety of Philanthotoxins on AMPAR Inhibition. Issue 8 (8th July 2014) - Franzyk, Henrik; Grzeskowiak, John W.; Tikhonov, Denis B.; Jaroszewski, Jerzy W.; Mellor, Ian R.
Abstract Philanthotoxin‐433 (PhTX‐433) is a known potent inhibitor of ionotropic glutamate receptors, and analogues have been synthesised to identify more potent and selective antagonists. Herein we report the synthesis of four PhTXs with a cyclopropane moiety introduced into their polyamine chain, and their inhibition of an α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor subtype by using two‐electrode voltage‐clamp assays on Xenopus oocytes expressing the GluA1flop subunit. All analogues were found to be more potent than PhTX‐343, with trans‐cyclopropyl‐PhTX‐343 being the most potent (∼28‐fold) and cis‐cyclopropyl‐PhTX‐343 least potent (∼4‐fold). Both cis‐ and trans‐cyclopropyl‐PhTX‐444 had intermediate potency (both ∼12‐fold). Molecular modelling indicates that a cyclopropane moiety confers a favourable steric constraint to the polyamine part, but this is compromised by a cis conformation due to enhanced intramolecular folding. Elongated PhTX‐444 analogues alleviate this to some extent, but optimal positioning of the amines is not permitted.